Chronic Active Antibody-Mediated Rejection Is Associated With the Upregulation of Interstitial But Not Glomerular Transcripts - Trailin, Andriy; Mrazova, Petra; Hruba, Petra; Voska, Ludek; Sticova, Eva; Slavcev, Antonij; Novotny, Marek; Kocik, Matej; Viklicky, Ondrej (Frontiers in Immunology, 2021)
Molecular assessment of renal allografts has already been suggested in antibody-mediated rejection (ABMR), but little is known about the gene transcript patterns in particular renal compartments. We used laser capture microdissection coupled with quantitative RT-PCR to distinguish the transcript patterns in the glomeruli and tubulointerstitium of kidney allografts in sensitized retransplant recipients at high risk of ABMR. The expressions of 13 genes were quantified in biopsies with acute active ABMR, chronic active ABMR, acute tubular necrosis (ATN), and normal findings. The transcripts were either compartment specific (TGFB1 in the glomeruli and HAVCR1 and IGHG1 in the tubulointerstitium), ABMR specific (GNLY), or follow-up specific (CXCL10 and CX3CR1). The transcriptional profiles of early acute ABMR shared similarities with ATN. The transcripts of CXCL10 and TGFB1 increased in the glomeruli in both acute ABMR and chronic active ABMR. Chronic active ABMR was associated with the upregulation of most genes (SH2D1B, CX3CR1, IGHG1, MS4A1, C5, CD46, and TGFB1) in the tubulointerstitium. In this study, we show distinct gene expression patterns in specific renal compartments reflecting cellular infiltration observed by conventional histology. In comparison with active ABMR, chronic active ABMR is associated with increased transcripts of tubulointerstitial origin.